Proceedings of the 4th Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2019) 2019
DOI: 10.2991/aisteel-19.2019.126
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing of Student’s Mathematics Critical Thinking Ability Through Problem Based Learning

Abstract: Critical thinking is a part of higher order thinking ability that require students to develop the process of analyzing or evaluating information on a problem based on logical thinking to determine decissions. But the fact in learning mathemathics, this ability is still not developed well, so that the aplication of problem based learning is expected to be a solution to increase student's mathematics critical thinking ability. The purpose of this study is to identity the increasing of students' mathematics criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Furthermore, the journals analyzed are journals published in the last seven years, namely 2013-2020. The effect size of each journal is presented in Table 2 (Hakim et al, 2014) 0.570 moderate effect J03 (Sari et al, 2014) 2.729 high influence J04 (Arifin et al, 2015) 0.656 moderate effect J05 (Waspadany et al, 2016) 1.867 high influence J06 (Warmi, 2017) 1.302 very high effect J07 (Yanti & Prahmana, 2017) 0.611 moderate effect J08 (Ilham, 2018) 0.763 high effect J09 (Marinda et al, 2018) 1.686 high influence J10 (Noer & Gunowibowo, 2018) 0.458 moderate effect J11 (Islahuddin et al, 2019) 0.476 moderate effect J12 (Putri & Fauzan, 2019) 0.966 high effect J13 (Sari et al, 2019) 1.075 high effect J14 (Sirait, 2019) 1.348 very high effect J15 (Steven et al, 2019) 0.450 moderate effect Average effect size 1.041 high effect…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the journals analyzed are journals published in the last seven years, namely 2013-2020. The effect size of each journal is presented in Table 2 (Hakim et al, 2014) 0.570 moderate effect J03 (Sari et al, 2014) 2.729 high influence J04 (Arifin et al, 2015) 0.656 moderate effect J05 (Waspadany et al, 2016) 1.867 high influence J06 (Warmi, 2017) 1.302 very high effect J07 (Yanti & Prahmana, 2017) 0.611 moderate effect J08 (Ilham, 2018) 0.763 high effect J09 (Marinda et al, 2018) 1.686 high influence J10 (Noer & Gunowibowo, 2018) 0.458 moderate effect J11 (Islahuddin et al, 2019) 0.476 moderate effect J12 (Putri & Fauzan, 2019) 0.966 high effect J13 (Sari et al, 2019) 1.075 high effect J14 (Sirait, 2019) 1.348 very high effect J15 (Steven et al, 2019) 0.450 moderate effect Average effect size 1.041 high effect…”
Section: Resultsmentioning
confidence: 99%
“…Many primary studies have been carried out in Indonesia to assess the PBL model's effect on junior high school students' critical thinking skills. Previous studies revealed that the implementation of PBL could enhance junior high school students' critical thinking skills (Arifin et al, 2015;Hakim et al, 2014;Ilham, 2018;Islahuddin et al, 2018;Marinda et al, 2018;Noer & Gunowibowo, 2018;Nurafiah et al, 2013;Putri & Fauzan, 2019;Sari et al, 2014;Sari et al, 2019;Sirait, 2019;Steven et al, 2019;Susanti & Suwu, 2016;Warmi, 2017;Waspadany et al, 2016;Yanti & Prahmana, 2017). However, the findings of the various studies are inconsistent, and the results in these studies do not yet include the value of the effect size of the PBL on students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Some empirical studies, however, revealed that PBL had a modest positive effect on students' MCTS (Hendriana et al, 2013;Islahuddin et al, 2018;Ratnawati et al, 2020;Sunaryo, 2014;Widada et al, 2019). Moreover, other empirical studies revealed that PBL had a weak positive effect on students' MCTS (Arifin et al, 2020;Marinda et al, 2018;Sari et al, 2020;Sumarmo, 2012). These findings indicate that the effect of PBL on students' MCTS is heterogeneous.…”
Section: Introductionmentioning
confidence: 93%